(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Co-existence of a malignant ovarian germ cell tumour with advanced pregnancy is rare and poses significant diagnostic challenges. Physiological changes of pregnancy, along with the mechanical and biochemical effects of a large adnexal mass, may mimic acute obstetric conditions and delay diagnosis. Case presentation: A 17-year-old primigravida at 27 weeks 3 days of gestation presented with progressive abdominal distension, orthopnoea, and oliguria for 10 days. She had hypertension (150/90 mmHg) with 2+ proteinuria, suggestive of severe pre-eclampsia. Imaging (ultrasound and MRI) revealed a large solid-cystic pelvi-abdominal mass (167 × 210 × 100 mm) with fat, calcifications, ascites, and bilateral pleural effusion. Cytology of ascitic and pleural fluid was negative for malignancy. Tumour markers showed markedly elevated AFP (2382 ng/mL) along with raised LDH, CA-125, and CEA. After receiving antenatal corticosteroids and magnesium sulphate, she had a spontaneous preterm vaginal delivery of a live female neonate (935 g). Subsequently, fertility-sparing staging laparotomy with left salpingo-oophorectomy, omentectomy, pelvic lymph node sampling, and peritoneal washings was performed with complete macroscopic cytoreduction. Result: Histopathology confirmed a mixed germ cell tumour comprising 90% grade 3 immature teratoma and 10% yolk sac tumour, classified as FIGO stage IA (pT1aN0). Postoperative tumour markers showed a rapid decline. The patient was started on adjuvant multi-agent chemotherapy along with a GnRH agonist for ovarian protection. Conclusion: A large adnexal germ cell malignancy can mimic hypertensive disorders of pregnancy, leading to diagnostic delays. Early use of imaging, appropriate interpretation of tumour markers in pregnancy, and a multidisciplinary approach are crucial for timely diagnosis, effective oncological management, and favorable maternal and neonatal outcomes.